Support material for additive manufacturing, and manufacturing method of additive manufacturing object and three-dimensional structure using the same
The support material, composed of a polyvinyl alcohol-based resin with sulfonic acid groups and biodegradable polyester, addresses adhesion and removal issues in additive manufacturing by forming a phase-separated structure that enhances adhesion and water solubility.
Patent Information
- Application Number
- JP2022511845
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-31
- Filing Date
- 2021-03-17
- Publication Date
- 2025-04-03
- Estimated Expiration
- 2041-03-17
AI Technical Summary
Existing support materials for additive manufacturing face challenges such as low adhesion to resins like ABS, issues with biodegradable polyester agglomerates during water washing, and difficulties in filament formation.
A support material comprising a polyvinyl alcohol-based resin with a sulfonic acid group or a salt-containing group, combined with a biodegradable polyester, which forms a phase-separated structure for improved adhesion and water solubility.
The support material exhibits excellent adhesion to various model materials, including PLA, ABS, PA, PETG, and PC, and is easily removable by water without insoluble aggregates, ensuring environmental sustainability.
Smart Images

Figure 0007656269000020 
Figure 0007656269000001 
Figure 0007656269000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a support material that has excellent adhesion to a three-dimensional structure to be additively manufactured, and that is also environmentally friendly because it is easy to remove and dispose of after additive manufacturing is completed, as well as to a method for manufacturing an additively manufactured object and a three-dimensional structure using the same. [Background technology]
[0002] Additive manufacturing is a method for creating a three-dimensional object with a specific structure, in which a fluid material is extruded, solidified, and then further material is layered on top of it to create the object. Although UV curing and fused deposition modeling have been proposed as additive manufacturing methods, fused deposition modeling is widely used due to its simple device structure.
[0003] Supporting materials are used to supplement parts that do not exist in the target three-dimensional structure when additively manufacturing a three-dimensional object. Since the supporting materials are unnecessary for the target three-dimensional structure in the obtained additively manufactured object, they need to be removed after the manufacturing process.
[0004] One simple method for removing the support material without damaging it is to dissolve it in a solvent. By using a water-soluble resin, polyvinyl alcohol resin (PVA resin), as the support material, the solvent can be water, making it safe and environmentally friendly.
[0005] On the other hand, PVA resins are hard and have poor impact resistance, and are not easily melt molded or melt filamentized. In order to be used as a support material, it is required to have flexibility and impact resistance so that it can be adapted to various shapes. Therefore, it has been proposed to add a thermoplastic elastomer such as styrene-ethylene-butylene-styrene block copolymer (SEBS) to impart flexibility to PVA resins (for example, International Publication No. WO 2015 / 182681, International Publication No. WO 2018 / 061694, and JP 2019-155917 A).
[0006] The above-mentioned support material has a sea-island structure with SEBS dispersed in a matrix (sea component) of PVA resin. Therefore, the waste liquid (aqueous solution of PVA resin) generated after dissolving PVA resin in water becomes a suspension state with water-insoluble SEBS dispersed, and since SEBS is not biodegradable, separate waste disposal is required.
[0007] From the viewpoint of recent green chemistry, the use of biodegradable polyester instead of non-biodegradable SEBS has been proposed in JP 2018-99788 A. Specifically, a composition containing a PVA-based resin containing 1,2-diol in a side chain and a biodegradable polyester is used as a support material for additive manufacturing, and such a support material has the advantage of having excellent adhesion to polylactic acid (PLA)-based resin, which is widely used as a material for additive manufacturing. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] International Publication No. 2015 / 182681 [Patent Document 2] International Publication No. 2018 / 061694 [Patent Document 3] JP 2019-155917 A [Patent Document 4] JP 2018-99788 A Summary of the Invention [Problem to be solved by the invention]
[0009] Although support materials made of a composition containing a PVA resin containing 1,2-diol in a side chain and a biodegradable polyester have advantages from the viewpoint of green chemistry, they have the following problems that prevent their widespread use: Problem 1: Although it has good adhesion to PLA resin, it has poor adhesion to other general-purpose resins such as ABS. Problem 2: When dissolving and removing in water, the biodegradable polyester, which has poor water solubility, produces aggregates that adhere to the model or cause clogging during the water washing process. Problem 3: When melting and filamenting, the filament diameter tends to fluctuate significantly.
[0010] The present invention has been made in consideration of the above circumstances, and has an object to provide a support material that has excellent adhesion to not only polylactic acid (PLA) but also acrylonitrile-butadiene-styrene copolymer (ABS), polyamide (PA), glycol-modified polyethylene terephthalate (PETG), and polycarbonate (PC) as model material materials used in additive manufacturing, that does not cause problems related to aggregates when washed away with water, that is easily dissolved and removed in water, and that does not interfere with environmental regulations even if the resulting waste liquid (PVA-based aqueous solution) is directly discharged and removed through wastewater treatment. [Means for solving the problem]
[0011] The supporting material for additive manufacturing of the present invention contains (A) a polyvinyl alcohol-based resin having a sulfonic acid group or a salt-containing group thereof; and (B) a biodegradable polyester.
[0012] The (A) polyvinyl alcohol-based resin having a sulfonic acid group or a salt-containing group thereof is a polyvinyl alcohol-based resin having, as the sulfonic acid group or a salt-containing group thereof, a structural unit represented by the following formula (3-1), (3-2), or (3-3). [ka]
[0013] In the formulae (3-1), (3-2) and (3-3), M is a hydrogen atom, an alkali metal or an ammonium group, and X and Y are intervening groups. The content of the structural units represented by (3-1), (3-2), and (3-3) is preferably 0.01 to 10 mol %. It is preferable that sodium acetate is contained in an amount of 0.5 to 2.0 parts by weight based on 100 parts by weight of the polyvinyl alcohol resin (A) having a sulfonic acid group or a salt-containing group thereof. The content of the (B) biodegradable polyester is preferably 5 to 100 parts by weight based on 100 parts by weight of the (A) polyvinyl alcohol resin having a sulfonic acid group or a salt-containing group thereof.
[0014] The polyvinyl alcohol-based resin (A) having a sulfonic acid group or a salt-containing group thereof and the biodegradable polyester (B) preferably have a phase-separated structure in which one is a matrix and the other is finely dispersed in the matrix, and more preferably have an island-in-sea structure in which the polyvinyl alcohol-based resin (A) having a sulfonic acid group or a salt-containing group thereof constitutes a sea component and the biodegradable polyester (B) is dispersed as island components. In a more preferred island-in-sea structure, the particle size of the domains of the biodegradable polyester (B) is 0.05 to 2 μm.
[0015] In the (B) biodegradable polyester, the ratio of aliphatic dicarboxylic acid units in the dicarboxylic acid units is preferably 40 to 80 mol %.
[0016] The supporting material for additive manufacturing of the present invention is preferably used as a supporting material for additive manufacturing of a fused deposition model. In this case, the supporting material for additive manufacturing is preferably in the form of a filament.
[0017] The present invention also includes an additive manufacturing object including the above-mentioned supporting material for additive manufacturing of the present invention, and a method for producing a three-dimensional structure using the supporting material for additive manufacturing.
[0018] The method for producing a three-dimensional structure of the present invention includes the steps of laminating the supporting material for additive manufacturing and the model material of the present invention in a molten state and solidifying them to produce an additive manufactured object; and bringing the additive manufactured object into contact with water.
[0019] The method for producing a three-dimensional structure of the present invention is suitable when the model material is polylactic acid, acrylonitrile-butadiene-styrene resin, polyamide resin, polyethylene terephthalate, or polycarbonate. Effect of the Invention
[0020] The supporting material for additive manufacturing of the present invention has excellent adhesiveness to various model materials and excellent water solubility, so that no insoluble aggregates are present in the waste liquid after washing and removal with water. Furthermore, since the supporting material is biodegradable, the waste liquid generated when the supporting material is washed and removed with water can be easily disposed of, and is environmentally friendly. [Brief description of the drawings]
[0021] [Figure 1] FIG. 2 is a diagram for explaining the measurement method performed in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] The configuration of the present invention will be described in detail below, but these are merely examples of preferred embodiments.
[0023] [Support material for additive manufacturing] The supporting material for additive manufacturing of the present invention contains (A) a polyvinyl alcohol (PVA) resin having a sulfonic acid group or a salt-containing group thereof, and (B) a biodegradable polyester.
[0024] (A) PVA resin having a sulfonic acid group or a salt thereof The PVA-based resin (A) having a sulfonic acid group or a salt-containing group thereof used in the support material of the present invention has excellent water solubility and melt moldability, and also has excellent compatibility with the other essential component of the support material, the biodegradable polyester (B). Therefore, it can be used as a filament-shaped support material, and when washed and removed with water after additive manufacturing, no polyester aggregates are generated, it can be easily dissolved and removed in water, and the resulting waste liquid can be easily treated as described below.
[0025] That is, the PVA resin having (A) a sulfonic acid group or a salt-containing group thereof has excellent compatibility with the biodegradable polyester (B) described later due to the sulfonic acid group or a salt-containing group thereof present in the molecule, and when the two components are melt-kneaded, the PVA resin having (A) a sulfonic acid group or a salt-containing group thereof and the biodegradable polyester (B) form a phase-separated structure in which one is a matrix and the other is finely dispersed in the matrix. Usually, when the component (A) is in the majority, the PVA resin as the component (A) forms a sea component, and the biodegradable polyester (B) forms an island-in-sea structure in which the biodegradable polyester is an island component. In the case of unmodified PVA resins and PVA resins containing 1,2-diol in a side chain, the polar groups present in the molecule are, in principle, only hydroxyl groups and acetyl groups, and therefore the compatibility with the biodegradable polyester (B) is low. Specifically, the dispersed particle size of the polyester resin as the island component in the PVA resin as the sea component is 2 to 5 μm, and when it is washed and removed with water, a large amount of 2 mm to 5 mm aggregates of the biodegradable polyester (B) are generated. Such aggregates adhere to the model material produced by layered manufacturing, or cause clogging of filter strainers for wastewater treatment, making wastewater treatment difficult. In this regard, when a PVA resin having a sulfonic acid group or a salt-containing group thereof is used, the compatibility is good, so that the biodegradable polyester (B) can be finely dispersed as domains (islands) of 0.05 to 2 μm, preferably 0.1 to 1.0 μm, and more preferably 0.1 to 0.5 μm in the phase separation structure (preferably a sea-island structure with a PVA resin matrix (sea) having a sulfonic acid group or a salt-containing group thereof). Therefore, the aqueous solution of the PVA resin produced by washing with water becomes a uniform milky liquid, and aggregates of the biodegradable polyester (B) are not generated. Therefore, the aggregates do not adhere to the model material, and do not clog during the filtration process of waste liquid treatment, and the waste liquid can be drained as is. Furthermore, since the polyester resin, which is the dispersoid, is biodegradable, the impact on the environment is reduced, and it is expected that the recent microplastic regulations can be avoided.
[0026] Here, the (A) PVA-based resin having a sulfonic acid group or a salt-containing group thereof refers to a PVA-based resin having a vinyl alcohol unit represented by the following general formula (1), which is a basic structural unit of the PVA-based resin, and in the case where the degree of saponification is less than 100%, further having a vinyl ester unit represented by the following general formula (2) which corresponds to an unsaponified portion, as well as a structural unit having a group having a sulfonic acid group or a salt-containing group thereof, represented by the following general formula (3-1), (3-2) or (3-3), in a side chain.
[0027] [ka]
[0028] [ka]
[0029] [ka]
[0030] The vinyl alcohol unit represented by the formula (1) and the vinyl ester unit represented by the formula (2) are derived from a vinyl ester compound used as a raw material monomer for PVA-based resins. Examples of vinyl ester compounds used as the vinyl ester monomer include vinyl formate, vinyl acetate, vinyl propionate, vinyl valerate, vinyl butyrate, vinyl isobutyrate, vinyl pivalate, vinyl caprate, vinyl laurate, vinyl stearate, vinyl benzoate, and vinyl versatate. From the viewpoint of economy, vinyl acetate is preferably used.
[0031] Therefore, in equation (2), R a R is an alkyl group having 1 to 18 carbon atoms, and depends on the vinyl ester compound used as a synthetic raw material for the PVA resin. a is preferably a methyl group, and a preferred vinyl ester unit is a vinyl acetate unit represented by the following formula (2a):
[0032] [ka]
[0033] In the formulas (3-1), (3-2), and (3-3), "-SO3M" (M is hydrogen, an alkali metal, or an ammonium group) corresponds to a sulfonic acid group-containing group when M is hydrogen, and corresponds to a salt-containing group when M is an alkali metal or ammonium. 1 , R 2 , R 3 , R 4 , R 5 , R 6 are each independently hydrogen or an alkyl group having 1 to 4 carbon atoms. X and Y are intervening groups, and are usually alkylene groups having 1 to 4 carbon atoms, ester bonds, amide bonds, ether bonds, etc. c may be hydrogen, an alkyl group, a sulfonic acid group or a salt thereof containing group ("--SO3M" (wherein M represents hydrogen or an alkali metal or ammonium group)), or a group containing -SO3M.
[0034] The structural unit having a sulfonic acid group or a salt-containing group thereof of the formula (3-1) is formed by using an unsaturated monomer having a sulfonic acid group or a salt-containing group thereof (hereinafter referred to as a "sulfonic acid group-containing unsaturated monomer") such as the following olefin sulfonic acid (4-1), sulfoalkyl (meth)acrylamide (4-2) or (4-3), or sulfoalkyl (meth)acrylate (4-4). The intervening groups X and Y are alkylene groups (-(CH2)n-), ester bonds (-COO-), carbonyl bonds (-CO-), amide bonds, or combinations thereof, depending on the type of sulfonic acid group-containing unsaturated monomer used.
[0035] [ka] [ka] [ka] [ka]
[0036] In the above formulas (4-1), (4-2), (4-3), and (4-4), R 11 , R 12 , R 13 , R 14 are each independently a hydrogen atom or an alkyl group having 1 to 4 carbon atoms, n is an integer of 2 to 4, and M is a hydrogen atom, an alkali metal, or an ammonium group.
[0037] The structural unit having a sulfonic acid group or a salt-containing group thereof of the formula (3-2) can be formed, for example, by using a sulfoalkyl maleate represented by the following formula as an unsaturated monomer containing a sulfonic acid group or the like.
[0038] [ka] [ka]
[0039] In the above formulas (5-1) and (5-2), n is an integer of 2 to 4, and M is a hydrogen atom, an alkali metal, or an ammonium group.
[0040] Furthermore, the structural unit having a sulfonic acid group or a salt-containing group thereof of the formula (3-3) is formed, for example, by using the following sulfoalkyl(meth)acrylamide as the unsaturated monomer containing a sulfonic acid group or the like.
[0041] [ka]
[0042] In the above formula (5-3), R 15 is hydrogen or an alkyl group having 1 to 4 carbon atoms, n is an integer of 2 to 4, and M is a hydrogen atom, an alkali metal, or an ammonium group.
[0043] Specific examples of the olefin sulfonic acid include olefin sulfonic acids such as vinyl sulfonic acid, allyl sulfonic acid, and methallyl sulfonic acid, and salts thereof. Specific examples of the sulfoalkyl malate include sodium sulfopropyl-2-ethylhexyl malate, sodium sulfopropyl-2-ethylhexyl malate, sodium sulfopropyl tridecyl malate, and sodium sulfopropyl eicosyl malate. Specific examples of the sulfoalkyl(meth)acrylamide include sodium sulfomethylacrylamide, sodium sulfo-t-butylacrylamide, sodium sulfo-S-butylacrylamide, and sodium sulfo-t-butylmethacrylamide. Further, specific examples of the above-mentioned sulfoalkyl (meth)acrylate include, for example, sodium sulfoethyl acrylate, etc. When the sulfoalkyl (meth)acrylate is introduced by copolymerization, among the above-mentioned sulfonic acid group-containing unsaturated monomers, olefin sulfonic acid or a salt thereof is preferably used.
[0044] The degree of saponification (measured according to JIS K 6726) of the PVA resin having a sulfonic acid group or a salt thereof used in the present invention is preferably 75 to 99 mol%, more preferably 80 to 95 mol%, and further preferably 85 to 90 mol%. If the degree of saponification is too low, the water solubility tends to decrease.
[0045] The average degree of polymerization of the (A) PVA resin having a sulfonic acid group or a salt thereof (measured in accordance with JIS K 6726) is preferably 150-4,000, more preferably 250-1,000, and further preferably 300-500. If the average degree of polymerization is too low, the melt viscosity tends to be low, which may lead to sagging during additive manufacturing, or to a decrease in filament strength, which may lead to fragility during modeling.On the other hand, if the average degree of polymerization is too high, the melt viscosity tends to be high, which may lead to difficulty in increasing the additive manufacturing speed when used as a filamentary support material, or to a decrease in the rate of removal by dissolution in water.
[0046] Furthermore, the content (modification rate) of structural units having a sulfonic acid group or a salt-containing group thereof in the (A) PVA-based resin having a sulfonic acid group or a salt-containing group thereof is preferably 0.01 to 10 mol%, more preferably 0.1 to 5 mol%, and particularly preferably 0.5 to 3 mol%. If the modification rate is too low, the electrostatic chargeability of the resin tends to decrease, and the protective colloid properties tend to decrease. This causes a decrease in compatibility with the (B) biodegradable polyester. If the modification rate is too high, the heat resistance of the support material tends to decrease, and synthesis of the PVA-based resin having a sulfonic acid group or a salt-containing group thereof tends to become difficult.
[0047] (A) PVA-based resin having a sulfonic acid group or a salt-containing group thereof can be produced by (1) a method of copolymerizing a vinyl ester-based monomer with an unsaturated monomer having a sulfonic acid group or the like, followed by saponification, (2) a method of polymerizing a vinyl ester-based monomer and a compound having a functional group such as an alcohol, aldehyde or thiol having a sulfonic acid group or a salt-containing group thereof in the presence of a chain transfer agent, followed by saponification, (3) a method of treating a PVA-based resin with bromine, iodine or the like, followed by heating in an acidic aqueous solution of sodium sulfite, (4) a method of heating a PVA-based resin in a concentrated aqueous solution of sulfuric acid, or (5) a method of acetalizing a PVA-based resin with an aldehyde compound having a sulfonic acid group or a salt-containing group thereof. Among these, from the viewpoints of safety and workability during production, it is preferable to (1) copolymerize a vinyl ester monomer with an unsaturated monomer containing a sulfonic acid group or the like, and then saponify the resulting polymer.
[0048] In addition to the vinyl ester monomers and oxyalkylene group-donating vinyl monomers, the PVA resins having sulfonic acid groups or salt-containing groups thereof that are the subject of the present invention may also be copolymerized with the following monomers (other monomers) in a range of, for example, 1 mol % or less: Examples of other monomers include olefins such as ethylene, propylene, isobutylene, α-octene, α-dodecene, and α-octadecene; hydroxyl group-containing α-olefins such as 3-buten-1-ol, 4-penten-1-ol, 5-hexen-1-ol, and 3,4-dihydroxy-1-butene, and derivatives thereof such as acylated products; unsaturated acids such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, maleic anhydride, itaconic acid, and undecylenic acid, salts thereof, monoesters, or dialkyl esters thereof; nitriles such as acrylonitrile and methacrylonitrile; and acrylamide. olefin sulfonic acids such as ethylene sulfonic acid, allyl sulfonic acid, methallyl sulfonic acid, or their salts; alkyl vinyl ethers; vinyl compounds such as dimethylallyl vinyl ketone, N-vinylpyrrolidone, vinyl chloride, vinyl ethylene carbonate, 2,2-dialkyl-4-vinyl-1,3-dioxolane, and glycerin monoallyl ether; substituted vinyl acetates such as isopropenyl acetate and 1-methoxyvinyl acetate, vinylidene chloride, 1,4-diacetoxy-2-butene, 1,4-dihydroxy-2-butene, and vinylene carbonate.
[0049] The method for copolymerizing the vinyl ester monomer with the above-mentioned unsaturated monomer containing a sulfonic acid group or the like, and further with other monomers added as necessary, is not particularly limited, and any known method such as bulk polymerization, solution polymerization, suspension polymerization, dispersion polymerization, or emulsion polymerization can be used, but solution polymerization is usually carried out. The method of feeding the monomer components during copolymerization is not particularly limited, and any method such as batch feeding, divided feeding, continuous feeding, etc. may be used. Solvents used in such copolymerization usually include lower alcohols such as methanol, ethanol, isopropyl alcohol, n-propanol, and butanol, and ketones such as acetone and methyl ethyl ketone, and industrially, alcohols having 1 to 3 carbon atoms, particularly methanol, are preferably used. The amount of the solvent used may be appropriately selected in accordance with the degree of polymerization of the target copolymer, taking into consideration the chain transfer constant of the solvent. For example, when the solvent is methanol, the amount is selected from the range of S (solvent) / M (monomer)=0.01 to 10 (mass ratio), preferably about 0.05 to 3 (mass ratio).
[0050] A polymerization catalyst is used in the copolymerization, and examples of such a polymerization catalyst include known radical polymerization catalysts such as azobisisobutyronitrile, acetyl peroxide, benzoyl peroxide, and lauryl peroxide, and low-temperature active radical polymerization catalysts such as azobisdimethylvaleronitrile and azobismethoxydimethylvaleronitrile. The amount of the polymerization catalyst used varies depending on the type of catalyst and cannot be generally determined, but is selected according to the polymerization rate. For example, when azoisobutyronitrile or acetyl peroxide is used, the amount is preferably 0.01 to 1.0 mol %, particularly preferably 0.02 to 0.5 mol %, based on the vinyl ester monomer. The reaction temperature of the copolymerization reaction is from about 30°C to the boiling point depending on the solvent and pressure used, more specifically, from 35 to 150°C, preferably from 40 to 75°C.
[0051] The copolymer thus obtained is then saponified by dissolving the copolymer thus obtained in an alcohol or a water-containing alcohol and using an alkali catalyst or an acid catalyst. Examples of the alcohol include lower alcohols such as methanol, ethanol, propanol, and tert-butanol, among which alcohols having 1 to 3 carbon atoms, particularly methanol, are preferably used. The concentration of the copolymer in the alcohol is appropriately selected depending on the viscosity of the system, but is usually selected from the range of 10 to 60 mass%. Examples of the catalyst used for saponification include alkali catalysts such as hydroxides and alcoholates of alkali metals such as sodium hydroxide, potassium hydroxide, sodium methylate, sodium ethylate, potassium methylate, and lithium methylate; and acid catalysts such as sulfuric acid, hydrochloric acid, nitric acid, metasulfonic acid, zeolite, and cation exchange resin.
[0052] The amount of the saponification catalyst used is appropriately selected depending on the saponification method, the target degree of saponification, etc., but when an alkali catalyst is used, the appropriate amount is usually 0.1 to 30 mmol, preferably 2 to 15 mmol, per mol of the total amount of the vinyl ester monomer and the unsaturated monomer containing a sulfonic acid group or the like. The reaction temperature for the saponification reaction is not particularly limited, but is preferably 10 to 60° C. (particularly, 20 to 50° C.).
[0053] In this manner, (A) the PVA resin having a sulfonic acid group or a salt thereof used in the present invention is obtained. The PVA-based resin having a sulfonic acid group or a salt-containing group thereof obtained as described above contains sodium acetate as a by-product during synthesis. The content of sodium acetate is 0.1 parts by weight or more, preferably 0.3 parts by weight or more, more preferably 0.5 parts by weight or more, and 2.0 parts by weight or less, preferably 1.5 parts by weight or less, based on 100 parts by weight of (A) PVA-based resin having a sulfonic acid group or a salt-containing group thereof. The presence of sodium acetate at this level is preferable because the contact portion is slightly decomposed when the filament is melted, thereby improving the adhesion with the model material (material). That is, if the amount of sodium acetate is too small, the adhesion with the model material (material) tends to decrease. On the other hand, if the content of sodium acetate is too large, the thermal stability of the PVA-based resin tends to decrease, and during additive manufacturing, the support material may be easily altered or thermally deteriorated in the portion in contact with the additive manufacturing product of the model material material in a high temperature state, and the support material may even decompose and foam.
[0054] (B) Biodegradable polyester The biodegradable polyester used in the present invention refers to a polyester resin that satisfies the biodegradability specified by any one of ISO 14851, ISO 14855, ISO 9408, ISO 9439, ISO 10707, JIS K 6950, JIS K 6951, JIS K 6953, or JIS K 6955.
[0055] A polyester-based resin that can satisfy biodegradability contains an aliphatic diol unit represented by formula (11) and an aliphatic dicarboxylic acid unit represented by formula (12) as essential components, and further contains an aromatic dicarboxylic acid unit represented by formula (13) or a unit derived from a hydroxycarboxylic acid represented by formula (14) depending on the desired properties such as biodegradability, mechanical properties, and melt moldability.
[0056] [ka] [ka] [ka] [ka]
[0057] In the formulae (11), (12) and (14), p, q and r each independently represent an integer of 2 to 10, preferably an integer of 2 to 6. In addition, in the formula (13), Ar represents an aromatic ring.
[0058] The aliphatic diol derived from formula (11) generally has 2 to 10 carbon atoms, such as ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,4-cyclohexanedimethanol, etc. Among these, diols having 2 to 4 carbon atoms are preferred, ethylene glycol and 1,4-butanediol are more preferred, and 1,4-butanediol is particularly preferred.
[0059] The aliphatic dicarboxylic acid derived from the formula (12) generally has 2 to 10 carbon atoms, and examples thereof include succinic acid, adipic acid, suberic acid, sebacic acid, dodecanedioic acid, etc. Among these, adipic acid is preferred.
[0060] Examples of aromatic dicarboxylic acids derived from formula (13) include terephthalic acid, isophthalic acid, and naphthalenedicarboxylic acid, among which terephthalic acid and isophthalic acid are preferred, and terephthalic acid is particularly preferred.Furthermore, aromatic dicarboxylic acids in which a part of the aromatic ring is substituted with a sulfonate salt are also included.
[0061] Examples of hydroxycarboxylic acids derived from the formula (14) include 4-hydroxybutyric acid, 5-hydroxyvaleric acid, and 6-hydroxyhexanoic acid.
[0062] The (B) biodegradable polyester used in the present invention is not limited to one type of each of the aliphatic diol unit, aliphatic dicarboxylic acid unit, and aromatic dicarboxylic acid unit that are constituent units, and may contain a plurality of different types. In addition to the above diol units and dicarboxylic acid units, the copolymer may contain structural units derived from dicarboxylic acid units in which q and r are less than 2, such as structural units derived from oxalic acid, malonic acid, glycolic acid, and lactic acid, as long as the structural units do not impair biodegradability.
[0063] Specific examples of the biodegradable polyester (B) used in the present invention include polybutylene succinate (PBS), which has 1,4-butanediol as a basic structural unit, polybutylene succinate adipate (PBSA), polybutylene succinate lactate (PBSL), polybutylene adipate terephthalate (PBAT), and polyethylene succinate (PES).
[0064] Commercially available products may be used, such as "Ecoflex" (trade name) manufactured by BASF, which contains as its main component a condensation polymer of adipic acid / terephthalic acid and 1,4-butanediol, "GS-PLA" manufactured by Mitsubishi Chemical Corporation, which contains as its main component a condensation polymer of succinic acid / 1,4-butanediol / lactic acid, as well as Bionolle (trade name) manufactured by Showa Polymer Co., Ltd., Lunale (trade name) manufactured by Nippon Shokubai Co., Ltd., Biomax (registered trademark) manufactured by DuPont, and EasterBio (registered trademark) manufactured by Eastman Chemical Company.
[0065] The (B) biodegradable polyester used in the present invention is preferably a biodegradable polyester in which the content of aliphatic dicarboxylic acid units among the dicarboxylic acid units is 40 to 80 mol %, preferably 50 to 70 mol %. The dicarboxylic acid units include aliphatic dicarboxylic acid units and aromatic dicarboxylic acid units. By setting the ratio of the aliphatic dicarboxylic acid units within the above range, the mechanical strength, particularly the flexibility, tear strength, and impact resistance, are increased, and therefore it is preferable for the (B) biodegradable polyester to be used for the filamentary support material.
[0066] (B) The melt flow rate (MFR) of the biodegradable polyester is usually 1.0 g / 10 min or more, preferably 2.0 g / 10 min or more, most preferably 3.0 g / 10 min or more, and the upper limit is usually 6.0 g / 10 min or less, preferably 5.0 g / 10 min or less, and more preferably 4.0 g / 10 min or less, when measured at 190 ° C. and with a load of 2.16 kg. If the MFR is less than 1.0 g / 10 min, the fluidity during melting is poor, which is not preferable in terms of the relationship between the modeling speed during additive manufacturing of the support material and the modeling speed of the model material. On the other hand, if the MFR is more than 6.0 g / 10 min, the support material is likely to drip from the orifice.
[0067] The weight-average molecular weight of the biodegradable polyester (B) is usually 5,000 to 50,000, preferably 5,500 to 40,000, and particularly preferably 6,000 to 30,000. If the weight-average molecular weight is too large, the melt viscosity increases, and when a filament-shaped support material is formed by melt kneading, linear fluctuation of the filament occurs, and the wire diameter tends to be unstable. On the other hand, if the weight-average molecular weight is too small, the biodegradable polyester (B) is rejected on the filament surface during the production of the filament by melt kneading, and sheath-shaped insoluble matter remains when the support material is dissolved and removed in water, and the residue may adhere to the model material or cause clogging during wastewater treatment.
[0068] The content of the (B) biodegradable polyester in the support material is preferably 5 to 100 parts by weight, more preferably 10 to 60 parts by weight, and even more preferably 20 to 50 parts by weight, relative to 100 parts by weight of the (A) PVA-based resin. If the content of the (B) biodegradable polyester is too low, the flexibility of the filament as the support material decreases, the filament becomes more likely to break during modeling, and the adhesiveness to the layered product during layered modeling tends to decrease. On the other hand, if the content of the (B) biodegradable polyester is too high, not only does the water solubility decrease, but it becomes difficult to form a sea-island structure in which the (A) PVA-based resin having a sulfonic acid group or a salt-containing group thereof serves as the sea component, and it tends to become difficult to finely disperse the (B) biodegradable polyester in the sea-island structure in which the (A) PVA-based resin having a sulfonic acid group or a salt-containing group thereof serves as the sea component. These phenomena cause problems in the treatment of waste liquid generated by washing when the support material is washed and removed with water.
[0069] (C) Other ingredients (C-1) Other PVA-based resins The PVA-based resin contained in the support material of the present invention may contain a PVA-based resin other than the PVA-based resin having a sulfonic acid group or a salt-containing group (A), such as an unmodified PVA-based resin or another modified PVA-based resin, as long as the compatibility with the biodegradable polyester (B) is not impaired (specifically, 30% by weight or less of the total PVA-based resin, and preferably 10% by weight or less).
[0070] (C-2) Filler The support material of the present invention may contain a filler from the viewpoint of the strength of the support material. The filler is preferably biodegradable. Examples of biodegradable fillers include starch, cellulose, and biodegradable plastics. The average particle size of such fillers is usually 0.1 to 50 μm, more preferably 5 to 30 μm, and particularly preferably 10 to 20 μm. If the filler is too small, it tends to be difficult to knead it into the resin, and if the filler is too large, it not only causes surface roughness and a decrease in strength, but also requires the separation and removal of dispersoids made of filler contained in the waste liquid (PVA-based resin aqueous solution) generated by washing and removing it with water. The average particle size here is the particle size D measured by laser diffraction method. 50 Refers to...
[0071] The content of the filler in the support material is preferably 0.3 to 40% by weight, more preferably 2 to 30% by weight, and particularly preferably 5 to 10% by weight. If the content is too low, the effect of including the filler tends not to be obtained, whereas if the content is too high, the smoothness of the surface of the support material tends to decrease, and the strength tends to decrease.
[0072] (C-3) Other ingredients The support material of the present invention may contain a plasticizer, but from the viewpoint of molding stability, the content of the plasticizer is preferably small, specifically, 20% by weight or less, more preferably 10% by weight or less, further preferably 1% by weight or less, and particularly preferably 0.1% by weight or less. In addition to the above components, known additives such as antioxidants, colorants, antistatic agents, UV absorbers, lubricants, and other thermoplastic resins may be appropriately blended in. However, it is preferable to use biodegradable additives for these additives so as not to impair the ease of disposal and environmental compatibility of the support material of the present invention.
[0073] <Support material for additive manufacturing and its manufacturing method> The supporting material for additive manufacturing of the present invention (hereinafter sometimes simply referred to as the supporting material) contains (A) a PVA-based resin having a sulfonic acid group or a salt-containing group thereof, and (B) a biodegradable polyester.
[0074] The support material of the present invention can be provided as a uniformly mixed pellet-shaped composition by adding the above-mentioned components in a predetermined amount and kneading them in a heated and molten state in a twin-screw extruder. Preferably, the pellet-shaped composition is melt-kneaded in a single-screw extruder, extruded into a filament shape, cooled, and wound on a reel to provide the support material.
[0075] Specifically, the pellet-shaped composition obtained by melt-kneading in a twin-screw extruder is heated, melt-kneaded in a single-screw extruder, extruded from a single-hole or multi-hole strand die into a filament having a diameter of 1.5 to 3.0 mm, cooled and solidified by air cooling, and then wound on a reel. Such a filament-shaped support material is convenient because it can be sent out from the head together with the desired model material during additive manufacturing. In the case of a filament-shaped support material, flexibility and toughness to the extent that it does not break during the winding process of the reel, and rigidity to the extent that it can be sent out to the head without delay during additive manufacturing are required, and the support material of the present invention can satisfy these requirements.
[0076] The support material of the present invention obtained as described above has a phase-separated structure in which (A) PVA resin having a sulfonic acid group or a salt-containing group thereof and (B) biodegradable polyester are finely dispersed in the matrix, one of which is a matrix. It preferably has a sea-island structure in which (A) PVA resin having a sulfonic acid group or a salt-containing group thereof is a sea component and (B) biodegradable polyester is finely dispersed in the island component. The particle size of the (B) biodegradable polyester domains is preferably 90% or more, more preferably all domains, usually about 0.05 to 2 μm, preferably 0.1 μm to 1.0 μm, more preferably 0.1 to 0.5 μm, when observed in a field of view of 0.01 mm x 0.01 mm using a SEM (electron microscope) under the following conditions.
[0077] Equipment: JSM-6060LA (manufactured by JEOL) Acceleration voltage: 5 kV Spot size: 30 Stage angle: 0 degree Observed image: Secondary electron image Pretreatment: Etch with chloroform (60℃ x 2hr), then vacuum dry for 24hr
[0078] [Method for producing laminated object and three-dimensional structure] The layered object of the present invention is an layered object obtained when a three-dimensional structure (model material) having a desired shape is layered using the supporting material of the present invention, and is an integral structure of the supporting material and the model material.
[0079] The method for producing a three-dimensional structure of the present invention is a method for producing a three-dimensional structure (model material) having a desired shape using the supporting material of the present invention, and includes the steps of: laminating the supporting material for additive manufacturing and the model material of the present invention in a molten state, and solidifying the material to produce an additive manufactured object; and bringing the additive manufactured object into contact with water.
[0080] Examples of constituent materials (thermoplastic resins) of model materials to which the support material of the present invention can be applied include polylactic acid (PLA), acrylonitrile-butadiene-styrene copolymer (ABS), polyamide (PA), polycarbonate (PC), polyethylene terephthalate (PET), glycol modified polyethylene terephthalate (PETG), polyhydroxyalkanoate (PHA), wood filled composite materials, metal filled composite materials, carbon fiber filled composite materials, polyvinyl butyral (PVB), thermoplastic elastomers (TPE), thermoplastic polyurethanes (TPU), polyolefins, polypropylene (PP), acrylonitrile styrene acrylate (ASA), polyacrylate, polymethacrylate, polystyrene (PS), polyoxymethylene (POM), and mixtures thereof. The support material of the present invention has excellent adhesive properties, particularly with PLA, ABS, PA, PETG, and PC, and is therefore particularly excellent as a support material for these model materials.
[0081] In the method for producing a three-dimensional structure of the present invention, the additive manufacturing device for carrying out the step of producing an additive manufacturing object may be a fused additive manufacturing type additive manufacturing device having a plurality of heads capable of extruding the model material and the support material in a molten state, for example, a dual-head type FDM additive manufacturing device such as Create manufactured by Flashforge, Eagled manufactured by Rays Enterprises, MBot Grid II manufactured by 3D Systems, NJB-200W manufactured by Ninjabot, and EVO manufactured by Airwolf.
[0082] In the case of a fused deposition modeling printer, the model material, which is made up of the above-mentioned constituent materials, is usually formed into a strand or filament shape, like the support material, and provided in a wound state on a reel. The model material and the support material strand or filament are supplied to separate heads of the additive manufacturing device, where they are heated and melted in the head, and laminated by being pressed against the stage.
[0083] The melt temperature at the head is usually 150 to 300°C, extrusion is performed at a pressure of 200 to 1000 psi, and the layer pitch is usually 100 to 350 µm.
[0084] The melt-extruded supporting material and modeling material are successively cooled and solidified, and newly melt-extruded supporting material and modeling material are layered on top and solidified, forming an additive object containing the desired modeling material.
[0085] The step of bringing the layered object into contact with water is a step of washing and removing the support material from the layered object composed of a support material having a three-dimensional shape and a model material. The method of washing and removing the support material may involve immersion in water or warm water in a container, or washing with running water. When immersing, stirring or ultrasonic waves may be applied to shorten the removal time. The water temperature is preferably about 25 to 80°C. For dissolving and removing, water or warm water in an amount of about 10 to 10,000 times the weight of the support material is used. By removing the support material from the layered object, a model material (three-dimensional structure) with a complex three-dimensional structure is obtained.
[0086] In the wastewater (PVA-based resin aqueous solution) generated by the water washing removal, the water-insoluble component (B) biodegradable polyester is finely dispersed as a dispersoid. However, the wastewater (PVA-based resin aqueous solution) generated by the water washing removal is about a suspension in which the (B) biodegradable polyester is dispersed with an average particle diameter of 0.1 to 5 μm, preferably 0.2 to 2 μm. Therefore, it can be disposed of (discharged) as it is without any special separation treatment. Since it can be discharged, a water washing removal method using running water that uses a relatively large amount of water (warm water) can be preferably adopted. EXAMPLES
[0087] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples as long as it does not depart from the gist of the invention. In the examples, "parts" refers to parts by weight.
[0088] [Measurement and evaluation method] 1. Characteristics of modified PVA resin (1) Saponification degree It was determined by analyzing the amount of alkali consumption required for hydrolysis of the remaining vinyl acetate units. In the case of side-chain 1,2-diol modified PVA resin, it was determined by analyzing the amount of alkali consumption required for hydrolysis of the remaining vinyl acetate units and 3,4-diacetoxy-1-butene structural units.
[0089] (2) Degree of polymerization It is expressed as the number-average degree of polymerization calculated from the viscosity (mPa s) of a 4% aqueous solution at 20°C measured in accordance with JIS K6726.
[0090] (3) Degree of denaturation The modified group (the amount of structural units having a sulfonic acid group or a salt thereof, or the amount of side chain 1,2-diol-containing groups) 1Calculation was performed from the integral value measured by H-NMR (300 MHz proton NMR, d6-DMSO solution, internal standard: tetramethylsilane, 50° C.).
[0091] 2. Characteristics of support materials (1)(B) Particle size of biodegradable polyester domain The prepared support material was observed under SEM (field of view: 0.01 mm x 0.01 mm) under the conditions below, and the particle size of the biodegradable polyester domain (PBAT domain) (B) was measured. Equipment: JSM-6060LA (manufactured by JEOL) Acceleration voltage: 5 kV Spot size: 30 Stage angle: 0 degree Observed image: Secondary electron image Pretreatment: Etch with chloroform (60℃ x 2hr), then vacuum dry for 24hr
[0092] (2) Linear diameter stability The diameter of the filament of the filament-shaped support material (diameter 2.85 mm) was measured at 15 points at 1 m intervals along the length of the material, and the results are shown as deviations from the specified diameter of 2.85 mm. The smaller the deviation, the better the wire diameter stability.
[0093] 3. Adhesion to model materials The model materials used were polylactic acid (PLA), ABS resin (ABS), polyamide (PA), glycol-modified polyethylene terephthalate (PETG), and polycarbonate (PC), and their adhesion to the filamentous support materials was evaluated as follows. The support material obtained above and filaments of the above four types of model material were set in the nozzle head of an FDM-type dual-head 3D printer (EVO manufactured by Airwolf3D), and the layered object shown in Figure 1 was created. In Figure 1, 1 is a model made of the support material, and 2 is an L-shaped model material created with the model material. The modeling status of this layered object was observed, and the adhesion on each surface was evaluated by manually peeling the model material from the model material on the surface (α surface) where the model material was layered on the model made of the support material and the surface (β surface) where the support material was layered on the model material. Adhesion was evaluated according to the following criteria A, B, and C. If the adhesion is such that the part can be peeled off by hand, additive manufacturing may not be successful if the modeling speed is increased.
[0094] A: It can be laminated and cannot be peeled off by hand after molding. B: It can be used for additive manufacturing, and after manufacturing, it can be easily peeled off by hand. C: Additive manufacturing is difficult
[0095] 4. Easy to clean (1) Water solubility (complete dissolution time) The support material was cut to a length of 2 mm, and 5 g of the cut pieces were placed in a 90 mesh wire basket. The wire basket was then immersed in a 500 ml water bath at 40°C and stirred at 300 rpm, and the time it took for the pellets on the wire basket to dissolve and disappear (time to complete dissolution: minutes) was measured. The shorter the time to complete dissolution, the better the water solubility. (2) Generation of aggregates If any insoluble matter or agglomerates remained on the wire mesh used in the water solubility test after 2 hours had passed, it was evaluated as having occurred, and if no agglomerates were visible on the wire mesh, it was evaluated as not having occurred.
[0096] [Production of modified PVA resin] (1) PVA-based resin 1 having a sulfonic acid group or a salt-containing group thereof (hereinafter referred to as "sulfonic acid-modified PVA-based resin 1") A reaction vessel equipped with a reflux condenser, a dropping funnel, and a stirrer was charged with 1,000 parts by weight of vinyl acetate, 422 parts by weight of methanol, 62 parts by weight of sodium allylsulfonate (3.7 mol % relative to vinyl acetate, chlorine content 0.26%), and 0.072 mol % (relative to the charged vinyl acetate) of azobisisobutyronitrile. The temperature was increased under a nitrogen stream with stirring, and polymerization was carried out under reflux.
[0097] During the polymerization, azobisisobutyronitrile was added 4 times at 0.072 mol% (relative to the vinyl acetate charged), and when the conversion rate of vinyl acetate reached 96.4%, 0.1 parts by weight of m-dinitrobenzene was added to terminate the polymerization. Next, unreacted vinyl acetate monomer was removed from the system by blowing in methanol vapor to obtain a methanol solution of the copolymer. The obtained methanol solution of the copolymer was diluted with methanol to a concentration of 55% and charged into a kneader. While maintaining the solution temperature at 35°C, a methanol solution of sodium hydroxide (2% sodium concentration) was added at a ratio of 8 mmol per mol of vinyl acetate structural unit in the copolymer to perform saponification. As the saponification proceeded, the saponified product precipitated, and was filtered out when it became particulate. The obtained particles were thoroughly washed with methanol and then dried in a hot air dryer to obtain a resin composition containing a PVA-based resin having a sulfonic acid group or a salt-containing group thereof and chlorine. The content of sodium acetate was 1.3 parts by weight per 100 parts by weight of the PVA-based resin having a sulfonic acid group or a salt-containing group thereof.
[0098] The resulting sulfonic acid modified PVA resin 1 had a degree of saponification of 87.3 mol %, a number average degree of polymerization of 250, and a content (modification content) of structural units having a sulfonic acid group or a salt-containing group thereof of 2.7 mol %.
[0099] (2) PVA-based resins 2, 3, 4, 5 having sulfonic acid groups or salt-containing groups (hereinafter referred to as "sulfonic acid-modified PVA-based resins 2, 3, 4, 5") In the production of sulfonic acid-modified PVA-based resin 1, the amount of sodium allylsulfonate added, the polymerization time, and the washing time of the resulting PVA-based resin having a sulfonic acid group or a salt-containing group thereof with methanol were changed to obtain the following sulfonic acid-modified PVA-based resins 2, 3, 4, and 5, which differ in modification rate, polymerization degree, and amount of sodium acetate contained in the resin. Sulfonic acid modified PVA resin 2 Modification rate: 1.6 mol%, number average polymerization degree: 370, sodium acetate content per 100 parts of PVA resin: 0.9 parts Sulfonic acid modified PVA resin 3 Modification rate: 1.1 mol%, number average polymerization degree: 370, sodium acetate content per 100 parts of PVA resin: 0.9 parts Sulfonic acid modified PVA resin 4 Modification rate: 1.1 mol%, number average polymerization degree: 370, sodium acetate content per 100 parts of PVA resin: 0.2 parts Sulfonic acid modified PVA resin 5 Modification rate: 0.3 mol%, number average polymerization degree: 370, sodium acetate content per 100 parts of PVA resin: 0.8 parts
[0100] (3) Side-chain 1,2-diol modified PVA resin A reactor equipped with a reflux condenser, a dropping funnel, and a stirrer was charged with 85 parts of vinyl acetate (10% of the total amount was initially charged), 460 parts of methanol, and 7.6 parts of 3,4-diacetoxy-1-butene, and 0.32 parts of azobisisobutyronitrile was added. The temperature was raised under a nitrogen stream while stirring, and polymerization was initiated. Furthermore, 0.5 hours after the start of polymerization, 765 parts of vinyl acetate were dropped for 8 hours (drop rate 95.6 parts / hr). 2.5 hours and 4.5 hours after the start of polymerization, 0.2 parts of azobisisobutyronitrile were added, and when the polymerization rate of vinyl acetate reached 85%, a specified amount of m-dinitrobenzene was added to terminate the polymerization. Subsequently, the unreacted vinyl acetate monomer was removed from the system by distillation while blowing in methanol vapor, and a methanol solution of the copolymer was obtained.
[0101] Next, the solution was diluted with methanol to adjust the solid content concentration to 50%, and the methanol solution was charged into a kneader. While maintaining the solution temperature at 35°C, a 2% sodium content methanol solution in sodium hydroxide was added at a ratio of 9 mmol per mole of the total amount of vinyl acetate structural units and 3,4-diacetoxy-1-butene structural units in the copolymer to perform saponification. As the saponification proceeded, the saponified product precipitated and became particulate, and 4 mmol of a 2% methanol solution was added per mole of the total amount of vinyl acetate structural units and 3,4-diacetoxy-1-butene structural units to perform saponification. Thereafter, 0.8 equivalents of sodium hydroxide were added to acetic acid for neutralization, the mixture was filtered, thoroughly washed with methanol, and dried in a hot air dryer to obtain a PVA-based resin having a 1,2-diol structure in the side chain (side chain 1,2-diol modified PVA-based resin). The content of sodium acetate was 1.3 parts by weight per 100 parts by weight of the side chain 1,2-diol modified PVA-based resin.
[0102] The resulting side-chain 1,2-diol modified PVA resin had a degree of saponification of 86 mol %, a number average degree of polymerization of 380, and a content of 1,2-diol structural units in the side chain of 4 mol %.
[0103] [Creating support material] Support material No. 1-6: 100 parts of any one of the sulfonic acid modified PVA resins 1-5 produced above and (B) PBAT (BASF's "Ecoflex C1200") as a biodegradable polyester were mixed in the ratio shown in Table 1. The resulting blend was fed to a twin-screw extruder to obtain a pellet-shaped composition. The pellets were melt-kneaded using the single-screw extruder described below, extruded into filaments with a diameter of 2.85 mm, air-cooled on a belt, and wound on a reel to obtain a filament-shaped support material. Single screw extruder: Technovel SZW20GT-24MG-STD 20mmφ L / D=24 Extrusion temperature: C1 / C2 / C3 / H / D=190 / 210 / 220 / 220 / 220℃ Rotation speed: 40 rpm Discharge amount: 1.0kg / hr
[0104] Support material No. 7, 8: 100 parts of the side chain 1,2-diol-containing PVA resin synthesized above was dry blended with a biodegradable polyester (BASF's "Ecoflex C1200") in the ratio shown in Table 1, and the blend was treated in the same manner as support material No. 1 to produce a filament-shaped support material.
[0105] For the support materials No. 1-8 prepared above, the dispersibility of (B) the biodegradable polyester (particle size of the PBAT domain), the line diameter stability, the adhesion to the model material, and the removability by washing with water were measured and evaluated based on the above measurement and evaluation methods. The results are shown in Table 2.
[0106] [Table 1]
[0107] [Table 2]
[0108] As can be seen from Table 2, the support material (No. 1-6) using a PVA resin having a sulfonic acid group or a salt-containing group thereof (hereinafter abbreviated as "sulfonic acid-modified PVA resin") as the modified PVA resin had a finely dispersed state of the biodegradable polyester compared to the support material (No. 7, 8) using a side-chain 1,2-diol-modified PVA resin. Regarding removability by washing with water, the support material (No. 1-5) using a sulfonic acid-modified PVA resin did not generate aggregates and also took a shorter time to completely dissolve compared to the support material (No. 7, 8) using a side-chain 1,2-diol-modified PVA resin. When the degree of modification of the sulfonic acid-modified PVA-based resin was 0.3 mol % (No. 6), the effect of the sulfonic acid modification was insufficient, and it was difficult to obtain the desired removability by washing with water.
[0109] Furthermore, when creating filamentous support materials, the use of sulfonic acid-modified PVA-based resin as the material provided filamentous support materials with superior linear stability compared to the use of side-chain 1,2-diol-modified PVA (comparison of No. 1-6 with No. 7 and 8).
[0110] In addition, in terms of adhesion to model materials, the support materials using side-chain 1,2-diol modified PVA resins (Nos. 7 and 8) had poor adhesion to ABS, PA, PETG, and PC, especially on the β-surface, and were only compatible with a limited number of model materials, whereas the support materials using sulfonic acid modified PVA resins (Nos. 1-5, especially No. 1-4) had excellent adhesion to various model materials (PLA, ABS, PA, PETG, PC) and were highly versatile. This means that support materials using sulfonic acid modified PVA resins have a wide range of application for model materials that can be used for additive manufacturing.
[0111] Comparing No. 3 and No. 5, even if the modification rate, saponification degree, and polymerization degree are the same, if the amount of sodium acetate contained in the sulfonic acid modified PVA resin becomes too small, a difference in adhesiveness was observed between the α and β faces. When using it as a support material with a complex shape, it is preferable to adjust the amount of sodium acetate to 0.5 to 2.0 parts by weight per 100 parts by weight of PVA resin. [Industrial Applicability]
[0112] The supporting material for additive manufacturing of the present invention has excellent water solubility, the size of the insoluble residue is extremely small, and it is biodegradable, so it can be drained as is. Therefore, it is easy to wash and remove with water after additive manufacturing, and the waste liquid treatment after washing and removal with water is easy and environmentally friendly, so it is useful as a supporting material that is temporarily molded and then discarded. In addition, it exhibits excellent adhesion to a variety of materials, making it highly versatile as a support material.
Claims
1. (A) a polyvinyl alcohol-based resin having a sulfonic acid group or a salt thereof; and (B) Biodegradable polyester A supporting material for additive manufacturing comprising: The (A) supporting material for additive manufacturing contains 0.5 to 2.0 parts by weight of sodium acetate per 100 parts by weight of a polyvinyl alcohol-based resin having a sulfonic acid group or a salt-containing group thereof.
2. The additive manufacturing supporting material according to claim 1, wherein the polyvinyl alcohol-based resin (A) having a sulfonic acid group or a salt-containing group thereof is a polyvinyl alcohol-based resin having, as the sulfonic acid group or the salt-containing group thereof, a structural unit represented by the following formula (3-1), (3-2), or (3-3): 【Chemistry 3】 (wherein M is hydrogen or an alkali metal or ammonium group, and X and Y are intervening groups).
3. The additive manufacturing supporting material according to claim 2, wherein the content of the structural units represented by (3-1), (3-2), and (3-3) in the polyvinyl alcohol-based resin (A) having a sulfonic acid group or a salt-containing group thereof is 0.01 to 10 mol %.
4. The supporting material for additive manufacturing according to any one of claims 1 to 3, wherein the content of the biodegradable polyester (B) is 5 to 100 parts by weight relative to 100 parts by weight of the polyvinyl alcohol-based resin (A) having a sulfonic acid group or a salt-containing group thereof.
5. The supporting material for additive manufacturing according to any one of claims 1 to 4, wherein the (A) polyvinyl alcohol-based resin having a sulfonic acid group or a salt-containing group thereof and the (B) biodegradable polyester have a phase-separated structure in which one is a matrix and the other is finely dispersed in the matrix.
6. The supporting material for additive manufacturing according to claim 5, which has a sea-island structure in which the (A) polyvinyl alcohol-based resin having a sulfonic acid group or a salt-containing group thereof serves as a sea component and the (B) biodegradable polyester is dispersed as island components.
7. The supporting material for additive manufacturing according to claim 6, wherein the particle size of the domain of the biodegradable polyester (B) is 0.05 to 2 μm.
8. The supporting material for additive manufacturing according to any one of claims 1 to 7, wherein the biodegradable polyester (B) has a ratio of aliphatic dicarboxylic acid units in dicarboxylic acid units of 40 to 80 mol %.
9. The supporting material for additive manufacturing according to any one of claims 1 to 8, which is a supporting material for additive manufacturing of a thermal fusion lamination type.
10. The supporting material for additive manufacturing according to claim 9 , wherein the supporting material for additive manufacturing is in a filament shape.
11. A step of laminating the supporting material for additive manufacturing and the model material according to any one of claims 1 to 10 in a molten state and solidifying the material to produce an additive manufacturing object; and A step of contacting the layered object with water. A method for producing a three-dimensional structure comprising the steps of:
12. The method according to claim 11, wherein the model material is polylactic acid, acrylonitrile-butadiene-styrene resin, polyamide resin, polyethylene terephthalate, or polycarbonate.
13. A layered object comprising the supporting material for layered object manufacturing according to any one of claims 1 to 10.
Citation Information
Patent Citations
Soluble material for three-dimensional molding
JP2016078284A
3D printer and three dimensional molding method
JP2018086814A
Laminate molding support material
JP2018099788A
Support material for laminate shaping
JP2019155917A
Use of polyvinyl alcohol and low polarity polymer blends as support structures in 3D printing
JP2019531214A